PERSPEKTIF PERNYATAAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH MENURUT PANDANGAN HUKUM DAN SYARIAH (Studi Kasus pada UMKM Desa Banjarejo Panekan Magetan) - Nova Maulud Widodo; Sundaru Guntur Wibowo; Yana Dwi Christanti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
AbstractThe purpose of this study was to determine whether the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM) were able to be understood and practiced by SMEs in Banjarejo Village, Panekan District, Magetan District. The research method used is qualitative research by direct interviews with the owners of SMEs. The data in this study are primary data obtained from interviews with MSME owners. Based on the results of literacy that have been done, this study is different from previous studies. This research uses an approach through legal and sharia views. Given the Magetan Regency, especially in the village Banjarejo is a boarding school environment. The results of this study, the community, especially SMEs in Banjarejo Magetan do not know about the presence of SAK EMKM regulations as a guide in making MSME financial reports. There is a perception of community concerns about the use of SAK EMKM. Legal and sharia perceptions of the use of PSAK EMKM are not yet fully accepted. The community thinks that only large companies are effectively using SAK EMKM.